Exploring e-promotion in sport national governing bodies - Whitburn, D.; Karg, A.; Turner, P. (International Journal of Sport Management and Marketing, 2018)
This study used an exploratory approach to examine how Australian sport national governing bodies (NGBs) initiate, implement, and adopt e-promotion strategies. A conceptual framework was developed based on two models; the systems process model of organisational performance and an e-marketing orientation (EMO) framework. The framework was applied to a sample of five NGB cases. Data was collected via documentation and interviews with key organisational staff, and analysed using a qualitative coding process. The resources required for successful adoption of an e-promotion strategy and the goals NGBs attempt to obtain were identified and a suite of contemporary e-promotion activities and their uses synthesised. The research showed a higher level of e-promotion adoption and e-marketing orientation is likely to facilitate critical outcomes to enhance NGB success. As such, the study provides guidance on how to develop strategy and achieve outcomes for both NGBs and wider sport and not-for-profit organisations